Development of Cost-Effective Restriping Strategies using Standard Width and Wide Waterborne Paints on Asphalt Pavements in Hot and Humid Climates. Issue 9 (September 2021) - Mousa, Momen R.; Hassan, Marwa; Carlson, Paul; Davis, Jason; Mousa, Saleh R.
In Louisiana, most districts restripe their roadways using waterborne paints every other year; this strategy is questionable in relation to efficiency and economy. Previous studies show substantial variability in paint service life throughout the U.S.A., ranging between 0.25 and 6.2 years. Shortcomings in modeling the retroreflectivity of waterborne paints appear to significantly contribute to these variations as several studies predicted these values using degradation curves with a coefficient of determination (R 2 ) as low as 0.1. Therefore, the objective of this study was to develop new cost-effective restriping strategies using 4 in. and 6 in. wide waterborne paints (15 and 25 mils thickness) when applied on asphalt pavements in hot and humid climates. To achieve this objective, National Transportation Product Evaluation Program data were collected and analyzed to evaluate the field performance of waterborne paints commonly used in southern states of the U.S.A. and to develop a decision making model that may be used by transportation agencies to predict when to restripe their roadways. Results indicated that 4 in. wide standard paints exhibited service life up to four years depending on the line color, traffic and initial retroreflectivity, while 4 in. wide high build paints had a service life of at least three years. Based on a life-cycle cost analysis, it was concluded that Louisiana Department of Transportation and Development could restripe its district roads every three years instead of the current two-year period using the same product (4 in. or 6 in. wide) saving about $20 million or $2 million, respectively, every year when restriping a 5, 000-mi network.